Secondary angle closure glaucoma due to posterior scleritis in a case of empty sella syndrome - Mansoori, Tarannum (Nepalese Journal of Ophthalmology, 2020)
Introduction: We frequently come upon cases of posterior scleritis with secondary angle closure glaucoma. However, it can pose a diagnostic dilemma in a patient with bilateral disc edema along with unilateral angle closure glaucoma due to posterior scleritis. Case: We report a case of a 25 - year old male, who presented with the complaints of pain, redness and blurring of vision in the left eye for the last 3 days. On ocular examination, unaided visual acuity of the right eye was 6/6 and the best corrected in the left eye was 6/9 with - 6.25 D sphere. Apart from conjunctival congestion and shallow anterior chamber in the left eye, rest of the anterior segment evaluation in both the eyes were normal. On fundus evaluation, there was presence of disc edema in both the eyes. Intraocular pressure was 20 and 32 mm of Hg in the right and left eye respectively. Gonioscopy revealed open angles in the right eye and no visible angle structures in the left eye. B-Scan of the left eye showed a typical “T” sign suggestive of posterior scleritis. MRI brain revealed empty sella turcica. Conclusion: Empty sella turcica has been reported to present with the bilateral disc edema which, when accompanied with other entities such as Posterior scleritis can be misleading and the diagnosis can pose to be a challenge.